Diseño e implementación de los sistemas eléctrico, iluminación y de comunicaciones para el área de VP operaciones piso 1 en el edificio CCI de Davivienda (2023)
This degree project was developed from the need of the Davivienda bank to remodel one of its areas in the CCI building located at street 28 # 13ª – 15 with headquarters in the city of Bogotá, to be occupied by the vice presidency of operations , for this adaptation of the area, the design and implementation of the regulated, normal and lighting electrical systems was carried out, in turn a new structured cabling network (Voice, data) was implemented.